El personal de salud en la pandemia: trabajar en un umbral de riesgo permanente - Hudson, Juan Pablo (Pontificia Universidad Católica del Perú, 2021)
This article presents some of the most relevant findings of a qualitative research that included fifteen interviews with health workers (doctors, kinesiologists and nurses) who work in areas of care for patients with Covid-19 in public hospitals and private clinics in seven provinces of Argentina.The objective was to highlight the transformations in their daily routines, with a particular emphasis on the consequences that the emergence of new occupational risks brought. The main hypothesis states that since the emergence of the pandemic, health personnel, especially those working in the Intensive Care Units, began to work at a risk threshold. That is, in a daily relationship with an imminent or effective health catastrophe, which caused physical and psychosocial symptoms and sufferings even in the case of those that had a vast experience. If anything was intensely modified, it was the historical relationship with patients and their families, as well as with their co-workers, as a consequence of the unprecedented contagiousness of this virus and the permanent inclusion of new care protocols.

Este artículo presenta algunos de los hallazgos más relevantes de una investigación de corte cualitativa que incluyó quince entrevistas con trabajadores de la salud (médicos/as, kinesiólogos/as y enfermeras/os) que trabajan en áreas que atienden a enfermos de Covid-19 en hospitales públicos y clínicas privadas de siete provincias de la Argentina. El objetivo fue relevar cuáles fueron las transformaciones en sus rutinas cotidianas, con un particular énfasis en las consecuencias que trajo aparejado el surgimiento de nuevos riesgos laborales. La hipótesis principal afirma que desde el surgimiento de la pandemia el personal de salud, especialmente los que trabajan en las Unidades de Terapia Intensiva, comenzaron a trabajar en un umbral de riesgo, es decir, en una relación cotidiana con una inminente o efectiva catástrofe sanitaria, lo que provocó síntomas y padecimientos físicos y psicosociales aún en el caso de aquellos/as que contaban con una vasta trayectoria. Si algo se modificó intensamente ha sido la relación histórica con los pacientes y sus familiares, lo mismo que con sus compañeros/as de trabajo, como consecuencia de la inédita contagiosidad de este virus y la permanente inclusión de nuevos protocolos de cuidado.
Health personnel in the pandemic: working at a permanent risk threshold
Keywords: Health personnel; Occupational risk; Permanent emergency; Care protocols; COVID-19 (Enfermedad); Personal de salud; Riesgos del trabajo; Emergencia permanente; Protocolos de cuidado; https://purl.org/pe-repo/ocde/ford#5.04.00